The cranky day and other Thomas the Tank Engine stories - Awdry, W.; Awdry, W.; Mitton, David (New York : Random House, 2000)
Three stories about two train engines named Thomas and Percy.
Cranky bugs -- Put-upon Percy -- Lady Hatt's birthday party.
"Based on The railway series by the Rev. W. Awdry."
3.0
K-3.
K-3
Keywords: Railroads -- Trains -- Fiction; Thomas the Tank Engine (Fictitious character) -- Fiction; Railroads -- Fiction; Thomas the Tank Engine (Fictional character) -- Fiction